Early pubertal timing and adult adjustment outcomes: Persistence, attenuation, or accentuation?. (17th March 2018) - Senia, Jennifer M.; Donnellan, M. Brent; Neppl, Tricia K.
ABSTRACT: Early pubertal timing is associated with internalizing and externalizing problems during adolescence. However, few studies explicitly test whether early puberty is especially problematic for those with pre‐existing problems (i.e., accentuation) and little is known about whether the negative correlates of early pubertal timing persist past young adulthood. We address these questions using longitudinal data from up to 451 participants in the Iowa Youth and Families project (e.g., Ge, Conger, & Elder, 1996, 2001). We replicated and extended previous results reported for this sample during adolescence (e.g., early maturing boys and girls reported more substance use) and found some evidence for accentuation in adolescence for psychological distress and substance use. However, correlations between early puberty and adult outcomes assessed up to two decades later were largely indistinguishable from zero including attenuation effects. These results suggest that any negative correlates of early pubertal timing are attenuated by the fourth decade of life.